2002
DOI: 10.1016/s0895-7061(02)02956-4
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of chondroitin sulfate and osteopontin expression in angiotensin ii-dependent left ventricular hypertrophy1

Abstract: Reactivated expression of CSPG in the adult heart may be an important component of LV ECMP remodeling in LVH. Elevated cardiac OPN expression could mediate the alterations in LV ECMP pattern in Ang II-dependent LVH, thus contributing to the development of contractile dysfunction in young Ren2 rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
0
40
1
1
Order By: Relevance
“…The right ventricular myocyte-capacitance measurement was corroborated by morphometric determination of right ventricular myocyte dimensions which showed no significant difference between TGR27 and CTR groups concerning length and width of myocytes. This is in disagreement with the results of Rothermund et al (2002) who find in 10-week-old TGR27 an increase in cardiomyocyte width of the right ventricle, indicating the development of right ventricular hypertrophy. This discrepancy might be due to the method (hematoxylin-eosin stain-processed tissue sections) used by the authors which can introduce some distortion in measurement of cardiomyocyte dimensions (Gerdes 2002).…”
Section: Ventricular Morphometric Changes and Cardiomyocyte Sizecontrasting
confidence: 99%
“…The right ventricular myocyte-capacitance measurement was corroborated by morphometric determination of right ventricular myocyte dimensions which showed no significant difference between TGR27 and CTR groups concerning length and width of myocytes. This is in disagreement with the results of Rothermund et al (2002) who find in 10-week-old TGR27 an increase in cardiomyocyte width of the right ventricle, indicating the development of right ventricular hypertrophy. This discrepancy might be due to the method (hematoxylin-eosin stain-processed tissue sections) used by the authors which can introduce some distortion in measurement of cardiomyocyte dimensions (Gerdes 2002).…”
Section: Ventricular Morphometric Changes and Cardiomyocyte Sizecontrasting
confidence: 99%
“…Several studies have revealed that interstitial and perivascular fibrosis, along with extensive collagen types I and III deposition are present in Ren2 [47][48][49]. Increased cardiac renin and ANGII levels have been described in this transgenic rat model [46].…”
Section: Animal Modelsmentioning
confidence: 67%
“…Interestingly, elevated left ventricular osteopontin expression has been reported in the Ren2 rat model characterized by high myocardial ANGII concentrations [49]. Monoclonal antibodies directed against either osteopontin or aVb3 completely blocked the mitogenic effect of ANGII on cultured rat cardiac fibroblasts [58], suggesting that osteopontin mediates ANGII-induced fibroblast proliferation acting by an integrin-dependent pathway.…”
Section: Stimulation Of Fibroblast Proliferationmentioning
confidence: 94%
“…FN also induces increased formation of focal adhesions and costameres, which are sites of contact of extracellular matrix with integrins and associated cytoskeletal proteins associated with the Z-disks of the sarcomere (39). As in other models of hypertrophy, the hypertrophic response is accompanied by changes in gene expression, with increased expression of the natriuretic peptides atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) and fetal isoforms of sarcomeric proteins such as ␤-myosin heavy chain (␤MHC) and ␣-skeletal actin (␣SkA).The pathophysiological relevance of the FN-induced, integrin-mediated pathway is highlighted by the observation of increased deposition of FN in the extracellular matrix in animal models of cardiac hypertrophy and in patients with cardiac failure (5,20,22,29,42,45). The increased synthesis of FN is in part mediated by stimulation of cardiac fibroblasts by angiotensin II, produced in response to mechanical overload (11,20,26,52).…”
mentioning
confidence: 99%
“…The pathophysiological relevance of the FN-induced, integrin-mediated pathway is highlighted by the observation of increased deposition of FN in the extracellular matrix in animal models of cardiac hypertrophy and in patients with cardiac failure (5,20,22,29,42,45). The increased synthesis of FN is in part mediated by stimulation of cardiac fibroblasts by angiotensin II, produced in response to mechanical overload (11,20,26,52).…”
mentioning
confidence: 99%